Motivasi Melanjutkan Studi Ke Perguruan Tinggi Bagi Siswa SMA Desa Margosari - E. Ngestirosa Endang Woro Kasih; Ingatan Gulö; Neneng Sri Wahyuningsih; Rizma Amalia Saadah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Facilities and education costs mostly cause the availability of higher education for rural communities. These problems cause higher education not to be achieved for rural communities, especially in Margosari Village, Central Lampung District. Preliminary data from observations show that the level of higher education is still below the average number. The advanced level of the village economy does not support education, so the average population still receives secondary education. This community service activity aims to provide motivation and education about higher education. The techniques used in this activity are survey, face-to-face and discussion techniques. The survey results found a high motivation for young people in the village to continue their studies. From educational sharing activities and discussions, it was found that high motivation for higher education was not supported by an attitude of agreeing to continue higher education. Sharing education about higher education provides enlightenment that all levels of society can achieve higher education by selecting universities that provide low financing schemes and scholarship schemes.